If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 4x + -45 = 60 + -6x Reorder the terms: -45 + 5x + 4x = 60 + -6x Combine like terms: 5x + 4x = 9x -45 + 9x = 60 + -6x Solving -45 + 9x = 60 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. -45 + 9x + 6x = 60 + -6x + 6x Combine like terms: 9x + 6x = 15x -45 + 15x = 60 + -6x + 6x Combine like terms: -6x + 6x = 0 -45 + 15x = 60 + 0 -45 + 15x = 60 Add '45' to each side of the equation. -45 + 45 + 15x = 60 + 45 Combine like terms: -45 + 45 = 0 0 + 15x = 60 + 45 15x = 60 + 45 Combine like terms: 60 + 45 = 105 15x = 105 Divide each side by '15'. x = 7 Simplifying x = 7
| 5y+y=48 | | 1x-.30x=525 | | 16t-t-5s-9t= | | -18.99=x+6.23 | | 9w-w=48 | | 4x+3x=15 | | 15i-4f-17i+3f= | | x-19.8=-4.24 | | 6cos(x)+8sin(x)=0 | | 3(2x-3)-13=2(x-1) | | 2n-16=14 | | 9u-v-11u+v= | | xt(-100)=-99 | | 6.2+1.2=8.9x | | ax+bx-3=-8 | | d-14.2=-18.7 | | 10y-5z-y-3z= | | (3x-2)(5x+1)(x)= | | k-4/=3 | | 6y+33=-x+3 | | (5.8+4)-(7.2-9)= | | 2t+3=7 | | 30-4x=14-8x | | 1.04x+3.14=7.89 | | 17+90+x=18 | | 12-5r-2+4r= | | 4+6n=6+2n | | 2x-3+4x+11= | | 12x+6=2y-4 | | w=z^7-3z^6+13 | | 20(v+4)-4v=4(4v+1)-11 | | 7c+4b+3b+a+10c-5a= |